'Are you a union member?' Determinants and trends of subjective union membership in Italian society (1972–2013). (November 2015) - Frangi, Lorenzo; Barisione, Mauro
This article analyses so-called 'subjective union membership' among employees and non-employees in Italy between 1972 and 2013. Unlike trends drawn from administrative data ('objective membership'), subjective membership, based on the declaration of the respondent, takes into account respondents' awareness of being affiliated to a union, their sense of belonging and the social desirability of stating their membership status. Instrumental and ideational rationales inform our cross-sectional and longitudinal hypotheses. Using an ITANES pooled dataset based on 11, 073 observations over 40 years (1972–2013), two major findings emerge. First, only a minority of politically engaged left-wing individuals have maintained the same probability of declaring themselves union members since the early 1970s. Secondly, subjective membership has sharply decreased over time not only among employees, but also – in clear contrast to administrative data – among non-employees. Subjective measures are thus particularly useful in improving our understanding of union membership.